Can stigmatizing attitudes be prevented in psychology students?. (4th July 2021) - Pingani, Luca; Coriani, Sandra; Galeazzi, Gian Maria; Nasi, Anna Maria; Franceschini, Christian
Abstract: Background: Stigmatizing attitudes have been found among psychology students in many studies, and they are becoming more common with time. Aims: This study examines whether participation in clinical psychology lessons reduces levels of stigmatization in a population of psychology students and whether it leads to any change in stigmatization. Methods: The study is a pre/post evaluation of the effectiveness of clinical psychology lessons (63 hours of lectures) as a tool to fight stigma. The presence of stigmatizing attitudes was detected using the Italian version of the Attribution Questionnaire-27 (AQ-27-I). Stigmatization was described before and after the lessons with structured equation modeling (SEM). Results: Of a total of 387 students contacted, 302 (78.04%) agreed to be involved in the study, but only 266 (68.73%) completed the questionnaires at both t0 and t1. A statistically significant reduction was seen in all six scales and the total score on the AQ-27-I. The models defined by the SEM (pre- and post-intervention) showed excellent model fit indices and described different dynamics of the phenomenon of stigma. Conclusions: A cycle of clinical psychology lessons can be a useful tool for reducing stigmatizing attitudes in a population of students seeking a psychology degree.